The Sisters Network: A National African American Breast Cancer Survivor Advocacy Organization - Newman, Lisa A. (American Society of Clinical Oncology, 2009)
Founded in 1994 by an African American woman who was diagnosed with breast cancer only a few months earlier, the Sisters Network advocacy organization today has nearly 3,000 members in 35 chapters throughout the country.